Factors that influence the participation among women in Inspection Visual Acetic acid (IVA) test - Adyani, Kartika; Realita, Friska (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Cervical cancer is one of the main causes of death for women in the world, so an IVA examination is needed as an early detection to reduce the incidence. Low participation in IVA examinations is one of the causes of cervical cancer development and hinders early treatment. The purpose of this study is to analyze the factors that influence the participation of women of childbearing age in the IVA examination. This research is quantitative research with a cross-sectional design conducted in the working area of Puskesmas Cepiring Kendal (Public Health Center of Cepiring Kendal ). The subjects of this study are 236 women of childbearing age who were married for more than five years. The research instrument used is a questionnaire. The factors that were significantly associated with the exclusion of fertile women in the IVA examination were access to information (0.007), family support (0.001), support from medical officers (0.007), and support from relatives (0.066). The multivariable analysis shows that family support is a significant factor. Women of childbearing age who do not get family support have a 46.9 times risk of not taking IVA examinations. Abstrak: Kanker serviks merupakan salah satu penyebab utama kematian wanita di dunia sehingga diperlukan pemeriksaan IVA sebagai deteksi dini untuk menurunkan angka kejadian kanker serviks pada wanita. Rendahnya keikutsertaan dalam pemeriksaan IVA menjadi salah satu penyebab berkembangnya kanker serviks dan menghambat pengobatan sejak dini. Tujuan dari penelitian ini adalah menganalisis faktor yang mempengaruhi keikutsertaan wanita usia subur dalam pemeriksaan IVA. Penelitian ini merupakan penelitian kuantitafif dengan desain cross-sectional yang dilakukan di wilayah kerja Puskesmas Cepiring Kendal. Subyek penelitian ini adalah 236 wanita usia subur yang sudah menikah lebih dari 5 tahun. Instrumen penelitian menggunakan kuesioner. Faktor yang berhubungan secara signifikan dengan ketidakikutsertaan Wanita Usia Subur dalam pemeriksaan IVA adalah akses informasi (0,007), dukungan keluarga (0,001), dukungan petugas (0,007), dan dukungan teman (0,066). Analisis multivariabel menunjukkan dukungan keluarga merupakan faktor yang berpengaruh signifikan. Wanita usia subur yang tidak mendapatkan dukungan keluarga memiliki risiko 46,9 kali untuk tidak ikut pemeriksaan IVA.